2023
DOI: 10.3390/foods12132470
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Commercial Synbiotic Administered In Ovo and In-Water on Broiler Chicken Performance and Meat Quality

Abstract: The present study aimed to test the synbiotic PoultryStar® solUS delivered in ovo to evaluate its effect on hatchability, productive performance and meat quality, compared to its post-hatch administration in water. On the twelfth day of embryonic incubation, 1200 fertile eggs were divided into synbiotic groups injected with 2 mg/embryo (T1) and 3 mg/embryo (T2), a saline group injected with physiological saline and an uninjected control group (C). After hatching, 120 male chicks/group were reared and chicks fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In ovo feeding with Lactobacillus acidophilus and mannan-oligosaccharide, or their combination, significantly enhanced hatch weight without influencing hatchability or livability [ 36 ]. Hatchability was negatively influenced by in ovo synbiotic [ 37 ], which supports the present study findings. Supplying nutrients from outside during embryonic development advances gut development and enhances nutrient digestion and absorption.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In ovo feeding with Lactobacillus acidophilus and mannan-oligosaccharide, or their combination, significantly enhanced hatch weight without influencing hatchability or livability [ 36 ]. Hatchability was negatively influenced by in ovo synbiotic [ 37 ], which supports the present study findings. Supplying nutrients from outside during embryonic development advances gut development and enhances nutrient digestion and absorption.…”
Section: Discussionsupporting
confidence: 91%
“…For example, some studies suggest that synbiotics do not significantly impact poultry belly fat [ 29 , 72 ]. Whilst, one of the studies indicated synbiotics can boost broiler performance, economic gain, and feed conversion by reducing abdominal fat [ 37 ]. This research clearly indicates a potential link between synbiotic supplementation and a decrease in visible fat in broiler carcasses.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, in ovo application and the continued dietary use of a synbiotic ( E. faecium and a prebiotic inulin) were reported to be insufficient to promote overall (d 0–42) broiler performance [ 11 ]. Similarly, in ovo inoculation of different synbiotics on embryonic day 12 (E12) did not influence broiler performance post hatch [ 24 , 25 , 26 ]. However, the early introduction of these compounds was reported to have more pronounced effects on broiler performance under challenge conditions [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A particular focus is on treatments based on natural products, such as using prebiotics, probiotics and synbiotics to treat the gut microbiota ( Youssef et al, 2018 ; Mohammed et al, 2021 ). Because synbiotics are a synergistic combination of probiotics and prebiotics that promote the viability and implantation of beneficial microbes in the digestive tract and have been shown to improve or preserve intestinal morphology, they may be more effective than prebiotics and probiotics alone ( Tavaniello et al, 2023 ). Probiotics are designed to increase the growth of beneficial bacteria in the lower part of the intestine and inhibit the growth of harmful bacteria in the animal's digestive system.…”
Section: Introductionmentioning
confidence: 99%